Spatial relationships among hemodynamic, anatomic, and biochemical plaque characteristics in patients with coronary artery disease. (March 2021) - Varshney, Anubodh S.; Coskun, Ahmet U.; Siasos, Gerasimos; Maynard, Charles C.; Pu, Zhongyue; Croce, Kevin J.; Cefalo, Nicholas V.; Cormier, Michelle A.; Fotiadis, Dimitris; Stefanou, Kostas; Papafaklis, Michail I.; Michalis, Lampros; et al.
Abstract: Background and aims: We aimed to characterize the spatial proximity of plaque destabilizing features local endothelial shear stress (ESS), minimal luminal area (MLA), plaque burden (PB), and near-infrared spectroscopy (NIRS) lipid signal in high- vs. low-risk plaques. Methods: Coronary arteries imaged with angiography and NIRS-intravascular ultrasound (IVUS) underwent 3D reconstruction and computational fluid dynamics calculations of local ESS. ESS, PB, MLA, and lipid core burden index (LCBI), for each 3-mm arterial segment were obtained in arteries with large lipid-rich plaque (LRP) vs. arteries with smaller LRP. The locations of the MLA, minimum ESS (minESS), maximum ESS (maxESS), maximum PB (maxPB), and maximum LCBI in a 4-mm segment (maxLCBI4mm ) were determined along the length of each plaque. Results: The spatial distributions of minESS, maxESS, maxPB, and maxLCBI4mm, in reference to the MLA, were significantly heterogeneous within and between each variable. The location of maxLCBI4mm was spatially discordant from sites of the MLA ( p< 0.0001), minESS ( p  = 0.003), and maxESS ( p  = 0.003) in arteries with large LRP (maxLCBI4mm  ≥ 400) and non-large LRP. Large LRP arteries had higher maxESS (9.31 ± 4.78 vs. 6.32 ± 5.54 Pa; p  = 0.023), lower minESS (0.41 ± 0.16 vs. 0.61 ± 0.26 Pa; p  = 0.007), smaller MLA (3.54 ± 1.22 vs. 5.14 ± 2.65 mm 2 ; p  = 0.002), and larger maxPB (70.64 ± 9.95% vs. 56.70 ± 13.34%, p<0 .001) compared with non-large LRP arteries. Conclusions: There is significant spatial heterogeneity of destabilizing plaque features along the course of both large and non-large LRPs. Large LRPs exhibit significantly more abnormal destabilizing plaque features than non-large LRPs. Prospective, longitudinal studies are required to determine which patterns of heterogeneous destabilizing features act synergistically to cause plaque destabilization. Graphical abstract: Image 1 Highlights: The spatial relationship between plaque features of local endothelial shear stress (ESS), minimal luminal area (MLA), plaque burden (PB), and near-infrared spectroscopy (NIRS) lipid signal is unknown. Coronary arteries imaged with angiography and NIRS-intravascular ultrasound (IVUS) underwent 3D reconstruction and computational fluid dynamics calculations of local flow patterns. The spatial distributions of minESS, maxESS, maxPB, and maxLCBI4mm, in reference to the MLA, were significantly heterogeneous within and between each variable. The location of maxLCBI4mm was spatially discordant from sites of MLA, minESS, and maxESS in most arteries, but not discordant with the site of maxPB. There is significant heterogeneity between hemodynamic, anatomic, and biochemical coronary plaque features.